Kandungan Klorofil, Karotenoid, dan Vitamin C pada Beberapa Spesies Tumbuhan Akuatik - Kurniawan, Madha; Izzati, Munifatul; Nurchayati, Yulita (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
Aquatic plants have important role in water ecosystem. They serve as the main producer, oxygen suplier and heavy metal absorbtion. Beside that, aquatic plants also economically potencial, such as sources of chlorophyll, carotenoid and vitamin C. The aim of this experiment is to analize the content of total chlorophyll, carotenoids and vitamin C in 13 species of aquatic plants. It is expected that these plants maybe used for commercial purposes. The plants were collected from Rawa Pening, Genuk stream, and brackish water shrim pond in Kendal and Jepara. These chemical analysis were done by spectrophotometer, whereas vitamin C content was measured using iodometric titration method. Results indicated that the highest content of chlorophyl was resulted by Ipomoea aquatica, which is 22,1 mg/L. The highest content of carotenodid and vitamin C is resulted by Nymphaea sp., which were 3,42 mg/L and 14,1 mg/30 g respectively. It is concluded that Ipomoea aquatica and Nymphaea sp. have good commercial value as sources of pigment and vitamin C.